Relationship Visibility in Spaces of Networked Individualism: How Couples Navigate Contrasting Injunctive Norms of Visual Communication - Federico Lucchesi; Katharina Lobinger (Forum: Qualitative Social Research)
Visual communication of romantic partners on social network sites (SNSs) is tied to normative discourses addressing different reference groups. By sharing pictures of the couple (relationship visibility), partners legitimize their romantic bond, increase relationship satisfaction, or discourage alternative partners. Nevertheless, injunctive norms of visual communication on SNSs often emerge from individual-focused SNS affordances, encouraging self-centered visual sharing. Generally, SNSs are understood as sites of networked individualism where individuals relate to others while remaining focused on themselves. We examined the injunctive norms governing relationship visibility on SNSs, discussing how partners navigate the tensions between norms stemming from individual-focused SNS affordances and relational norms. We conducted 63 semi-structured pair and individual interviews with romantic partners (42 participants, 21 couples), using participatory visual elicitation techniques. In the attempt to balance individual autonomy with relational and audience expectations, we found that partners develop practices to navigate contrasting norms. Key norms concern the extent of shared visual cues, timing and selection of SNS spaces for couple pictures, volume of sharing, and rules for sensitive pictures to maintain privacy. We provide insights into the complex negotiations between individual-focused norms and relational norms of visual communication on SNSs.